SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN BERBASIS WEB MENGGUNAKAN METODE SAW PADA TOKO SERBA CURAH CINERE - Yeremias Dala Sula, Yohanes; Ariadi, Fadly (JUPIK : Jurnal Penelitian Ilmu komputer, 2024)
Serba Curah Store is a supplier of household needs and catering needs with a variety of products on offer. In its operations, Serba Curah stores often accept new employees to meet existing human resource needs. The process of hiring employees at serba curah stores is still done manually, so it takes a long time, and there is no system that can produce employee hiring decisions quickly and accurately. To assist the selection process for employee recruitment at the Serba Curah Store, a Decision Support System (SPK) is used. The Employee Recruitment Decision Support System was built using the PHP programming language with the CodeIgniter framework and MySQL database. The process of calculating selection results uses the Simple Additive Weighting (SAW) method based on predetermined criteria. The criteria used are work experience, education, age, height, interview, appearance and travel time. The use of a decision support system with the Simple Additive Weighting method provides 75% accuracy results. With the application system, the selection process can take place more quickly and the resulting decisions meet the predetermined criteria.